Efficacy and safety of Ciprofol for procedural sedation and anesthesia in non-operating room settings - Zhong, Jing; Zhang, Jinlin; Fan, Yu; Zhu, Min; Zhao, Xining; Zuo, Zhiyi; Zhou, Xiushi; Miao, Changhong (Journal of clinical anesthesia, 2023)
Ciprofol, a novel intravenous anesthetic, provides rapid recovery in patients undergoing colonoscopy. We aimed to examine the efficacy and safety of ciprofol in comparison with propofol for sedation or anesthesia in non-operating room settings including endoscopic submucosal dissection, endoscopic retrograde cholangiopancreatography, and flexible bronchoscopy (FB). Prospective, randomized, double-blind, parallel-group clinical trial. University-affiliated teaching hospital. We recruited 207 patients scheduled for an endoscopic procedure from October 2021 to December 2021. Patients were randomized into three groups according to the dose during induction (n = 69 each): 1) ciprofol 6 mg/kg/h, 2) ciprofol 8 mg/kg/h, or 3) propofol 40 mg/kg/h. Ciprofol or propofol was administered throughout the procedure. The primary outcome was the success rate of sedation or anesthesia for the procedures. Secondary outcomes included induction time, endoscope insertion time, recovery time, discharge time, incidence of drug-related adverse events (AEs), neurological and inflammatory outcomes. The procedure success rates in the three groups were 100%. The induction time in the 6 (3.3 ± 1.0 min) and 8 mg/kg/h (2.9 ± 0.6 min) ciprofol groups was longer than that in the propofol group (2.5 ± 0.6 min) only in patients undergoing FB (p = 0.004). The time for patients to be fully alert and discharged from the post-anesthesia care unit was comparable across the three groups (p > 0.05). The incidence of drug-related AEs in the propofol and 6 and 8 mg/kg/h ciprofol groups was 84.1%, 76.8%, and 79.7%. No pain on injection was reported by ciprofol groups. Neurological outcomes and inflammatory responses were comparable among the three groups. Ciprofol induced a level of sedation or anesthesia equivalent to that induced by propofol in non-operating room settings except for a prolonged induction time in patients undergoing FB. Ciprofol had a safety profile similar to that of propofol. No pain on injection was reported by ciprofol. •Ciprofol, a novel intravenous anesthetic, and propofol induced equivalent sedation or anesthesia in non-operating room settings.•Ciprofol had a similar safety profile to that of propofol.•No pain on injection was reported by the ciprofol groups.•Ciprofol and propofol anesthesia had similar neurological outcomes and inflammatory parameters.